Peranan Pemilik Tanah dalam Pelepasan Tanah Adat Untuk Mewujudkan Kepastian Hukum Demi Kepentingan dalam Pembangunan Fasilitas Publik - Asdar Djabbar (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2020)
This study aims to determine the role of land owners in the traditional land release and to find out the obstacles to releasing the land for legal certainty in the construction of public facilities. This study uses an normative and empirical juridical approach, which was carried out at the Office of the Higher Education Service Institute (LLDIKTI) Region XIV Papua-West Papua and the Central Faidoma Market (Darfuar) in Biak Numfor. Data were obtained through documentation, interviews and observations, and were then analyzed descriptively and qualitatively. The results showed that the community played an important role in the land release for legal certainty during the both public facilities, especially during decision making. The tribal chief represents his community when the deliberation between government agencies requiring land and land owners takes place in a friendly way without intimidation. Obstacles to the release are non-legal and legal constraints. Non-legal constraints consist of overlapping recognition of traditional land by several tribes, clans, and unclear boundaries of the land due to natural boundaries, and the lower compensation. Legal constraints consist of the difference in perception between the government and the local traditional community on whether the basic agrarian principle fits the traditional law culture